Innowacyjność w edukacji językowej a profesjonalizm nauczyciela - Droździał-Szelest, Krystyna (Neofilolog, 2019)
Innovation in language education, just as in any other discipline, is connected with changes whose primary goal is to make the process of language learning/language teaching more efficient. Examples of such innovations include, for instance, task based instruction, computer assisted language learning or the use of portfolio as a means of assessment. Innovation implies a new, qualitatively different perception of the language learning/ language teaching process, roles of teachers and learners, use of materials etc., hence it is believed to constitute a challenge for language teachers and their professionalism. The present article is an attempt to answer the question whether and to what extent the language teaching profession is actually prepared to deal with innovation.